Інклюзивна бібліотека як агент змін у суспільстві - Тюркеджи, Н. С.; Мар’їна, О. Ю.; Tiurkedzhy, N. S.; Marina, O. Yu. (Харків : ХДАК, 2023)
Інклюзивні бібліотеки в Україні стають ключовим агентом змін у сучасному суспільстві, особливо в умовах військового конфлікту. Стаття розкриває важливість ролі інклюзивних бібліотек у створенні інклюзивного простору для всіх громадян. Російсько-українська війна суттєво змінила соціокультурний контекст нашої держави, посиливши необхідність формування інклюзивного суспільства. Інклюзивні бібліотеки відіграють ключову роль у формуванні доступності та нормалізації ставлення до людей з інвалідністю. Результати цього дослідження вказують на те, що основні принципи інклюзивних бібліотек, зокрема доступність, рівноправ’я та соціальна інклюзія, впливають на формування доступності в суспільстві загалом. Використання коректних термінів і дефініцій щодо інвалідності є важливим для формування свідомості інклюзивного суспільства, а освіта та інформаційна доступність — ключові чинники в її забезпеченні. The relevance of the article: In the aftermath of the full-scale Russian-Ukrainian war, Ukraine faces a critical juncture in its societal evolution. The need for inclusivity and the role of libraries in fostering it have become central issues. The urgent demand to analyze the impact of this confl ict on the formation of an inclusive society in Ukraine needs to be studied. The purpose of the article. This article aims to scrutinize the infl uence of the Russian- Ukrainian war on the processes involved in shaping an inclusive society in Ukraine. It focuses particularly on shifts in the perception of inclusivity, the signifi cance of barrierfree environments, and the role of libraries in facilitating these changes. Presentation of the main topic. The article delves into the transformation of Ukraine’s societal landscape in the wake of the war. It highlights how the confl ict has infl uenced the conceptualization of inclusivity, emphasizing the importance of creating accessible environments and highlights the pivotal role of libraries as agents of changes in this context. Conclusions. The analysis reveals a profound impact of the war on Ukraine’s approach to inclusivity. It elucidates how societal perceptions have shifted, placing a newfound emphasis on the creation of barrier-free spaces. Furthermore, the study underscores the instrumental role that libraries have played and continue to play in fostering inclusive communities. The practical signifi cance. This article off ers insights into the evolving dynamics of inclusivity in post-war Ukraine. Policymakers, librarians, and community leaders can draw upon these fi ndings to implement strategies that promote inclusivity and develop barrier-free environments. Libraries, as vital community hubs, can take the lead in this transformation, bridging gaps and facilitating social integration in the midst of confl ict.
Inclusive library as an agent of changes in society
Тюркеджи Н. С. - https://orcid.org/0000–0001–6785-2900
Keywords: інклюзивне суспільство; роль бібліотек у формуванні інклюзивного середовища; безбар’єрний простір; інклюзивні бібліотеки в Україні; соціальна інтеграція під час війни; inclusive society; role of libraries in shaping inclusive environments; barrier-free spaces; inclusive libraries in Ukraine; social integration during conflict